Finance and growth: Time series evidence on causality - Peia, Oana; Roszbach, Kasper (Journal of Financial Stability, 2015)
This paper re-examines the empirical relationship between financial and economic development while (i) taking into account their dynamics and (ii) differentiating between stock market and banking sector development. We study the cointegration and causality between finance and growth for 22 advanced economies. Our time series analysis suggests that causality patterns depend on whether countries’ financial development stems from the stock market or the banking sector. We show that stock market development tends to cause economic development, while a reverse causality is mostly present between banking sector development and output growth. These findings indicate that the direction of causality between finance and growth is likely to be different at high levels of development.